Revealing the Success of Renita Enceng Gondok in Maintaining its Business Existence - Liana, Eka Wahyu; Nugroho S.S, Rr. Lulus Prapti; Triyani, Dian (Universitas Semarang, 2020)
This research was conducted at the Renita Eceng Gondok SME, Demakan, Banyubiru, Ambarawa, Semarang in the marketing and production section. The aim of this study is to explore the success of the Renita Eceng SME business in maintaining its existence. This study is a case study with triangulation of data sources, observation data, interviews, documentation, and narratives. Informant study is based on the appropriate principle and adequacy. There are 6 basic informant principles in this study. The results of this study indicate that the strategy of Renita Eceng Gondok in achieving success and maintaining its existence is paying attention on material quality and improve the skill of their employee (human resources). The way of Renita Enceng Gondok explores creative ideas in creating variety of superior Enceng Gondok handycrafts products is by looking for patterns from internet then they developed the pattern based on the instruction from the owner of Renita Eceng Gondok. These ideas were turn into shoes, sandals, paper towels, jars, trash bins, frame, miniatures, and glass for hotel construction, laundry baskets, and others. The government supports this SME by facilitating exhibitions, training in management, marketing, equipments, etc.